Modeling on bearing behavior and damage evolution of single-lap bolted composite interference-fit joints. (15th March 2019) - Hu, Junshan; Zhang, Kaifu; Xu, Yunwei; Cheng, Hui; Xu, Guanhua; Li, Hailin
Abstract: This paper deals with the modeling of bearing behavior and damage evolution of single-lap bolted composite interference-fit joints. Shear nonlinearity constitutive relations for composites are defined with the Ramberg-Osgood equation. The anisotropic damage model established on continuum damage mechanics incorporates extended 3D failure criteria and exponential damage evolution rule to describe damage initiation and material stiffness degradation, respectively. Numerical simulations of composite joints based on the proposed model under varying interference-fit sizes, bolt preload levels and composite layups are conducted and validated by experimental tests. Results show the interface voids of joint-hole in micro-scale left by hole-drilling would compensate part of the nominal interference-fit size and make the real fit sizes smaller than the numerical ones. The strain contours and hyperechoic strips detected in bearing specimens are accurately characterized by damage patterns in joint models, whereas the predicted load-displacement behavior shows over-conservative errors caused by excessive bolt inclination. The fiber breakage and matrix crushing in micro-morphology on the bearing plane are well captured in numerical model, suggesting robust ability of the proposed model in application.